Minyak Zaitun dan Kunyit untuk Mengurangi Gatal pada Pasien Hemodialisis: Studi Kasus - Kurniawati, Rizka Yudhit; Triyanto, Arifin; Sukardi, Sukardi (PSIK FKKMK UGM, 2024)
Background: Chronic kidney disease (CKD) is a progressive and irreversible renal dysfunction, where the kidneys fail to function properly, lead to the body’s inability to maintain metabolism and fluid-electrolyte balance. More than half of end-stage CKD patients exhibit pruritus-related issues. Pruritus (itchiness) can result in redness, lesions, sleep disturbances, fatigue, depression, decreased quality of life, and even death. Therefore, a proper management is necessary to reduce pruritus complaints.Objective: To confirm the benefit of olive oil and turmeric in alleviating pruritus.Case report: A patient, 63 years old, had been undergoing hemodialysis since 2021 and had complained of itchiness 1 month after hemodialysis sessions. For three months, the patient applied a mixture of olive oil and turmeric powder on the area where the itchiness were felt, in the frequency of once every 1-2 days at night.Outcome: The intensity of itching had decreased from scale of 7 to 4, provided more comfort and improved sleep quality. Both olive oil and turmeric powder had anti-inflammatory and antioxidant properties that reduced pruritus complaints.Conclusion: The combination of these two ingredients can be considered as one therapy option to alleviate pruritus complaints in CKD patients undergoing hemodialysis.INTISARILatar belakang: Chronic kidney disease (CKD) merupakan gangguan fungsi renal yang progresif dan irreversible sehingga tubuh gagal untuk mempertahankan metabolisme dan keseimbangan cairan elektrolit. Lebih dari setengah pasien CKD tahap akhir menunjukkan masalah pruritus (gatal). Pruritus dapat mengakibatkan kemerahan, lesi, gangguan tidur, kelelahan, depresi, penurunan kualitas hidup, bahkan kematian. Oleh karena itu, perlu penanganan untuk mengurangi keluhan pruritus. Tujuan: Mengetahui manfaat minyak zaitun dan kunyit terhadap pruritus pada pasien dengan CKD. Laporan kasus: Seorang pasien usia 63 tahun, menjalani hemodialisis sejak 2021 dan mengeluhkan pruritus (gatal) sejak 1 bulan menjalani hemodialisis. Selama tiga bulan pasien mengoleskan campuran minyak zaitun dan bubuk kunyit pada bagian tubuh yang terasa gatal, dengan frekuensi 1-2 hari sekali pada malam hari.Hasil: Intensitas gatal berkurang dari skala 7 ke 4, lebih nyaman dan dapat meningkatkan kualitas tidur. Minyak zaitun dan bubuk kunyit memiliki efek antiinflamasi dan antioksidan yang berperan dalam mengurangi keluhan gatal. Simpulan: Campuran kedua bahan ini dapat dijadikan sebagai salah satu terapi untuk mengurangi keluhan pruritus pada pasien CKD yang menjalani hemodialisis.Kata kunci: hemodialisis; kunyit; minyak zaitun; pruritus